Analisis Pengelolaan Aset Daerah Pada Dinas Pendidikan Dan Kebudayaan Kabupaten Kepulauan Meranti - Mashudi Karyadinata; Sri Maulidiah (UIR Press, 2021)
This research is based on conditions in which there are still many deficiencies in the management process, there are still many assets of the Meranti Islands Regency Education and Culture Office that have not been properly recorded and recorded, so that the true value of assets is difficult to know and the whereabouts of these assets are difficult to trace. Apart from that, the information regarding the reporting of assets at the agency is not accurate. As for the purpose of the research is to find out whether the management of regional assets at the agency has been running well in accordancewith the applicable regulations and what obstacles are faced in the implementation of regional asset management at the Department of Education and Culture of the Meranti Islands Regency. In this study, the authors used the theoretical concepts put forward by George R. Terry, planning, organizing, actuating and controlling. The form or method used in this research is qualitative. While the data collection technique is done through observation, interview and documentation methods. The results of this study indicate that the regional asset management at the Meranti Islands District Educationand Culture Office has not been fully implemented optimally as regulated in statutory regulations, especially in data collection on the number of regional assets owned and the systems and procedures for managing regional assets. This is due to the lack of Standard Operating Procedures (SOP), not having a warehouse where assets are stored, not having conducted an assessment and evaluation of asset managers and a lack of experts in regional asset management. For this reason, the Meranti Islands Regency Education and Culture Office should have a Standard Operating Procedure (SOP) forregional asset management, and have a special warehouse for storing regional assets. Assess and evaluate the performanceof the asset manager periodically/quarterly and give appreciation or appreciation to the performance of regional assetmanagers in spurring morale and increasing a sense of responsibility, involving asset managers in trainings and having a special Accounting Staff in charge of assets.